Types and Nature of Oral Feedback Given by Teachers on Students’ Speech - Lemma, Befikadu (Journal of Languages and Language Teaching, 2023)
Classroom oral feedback helps students to improve their English language performance. The purpose of this study is to examine English language teachers' attitudes toward different types and methods of providing feedback on students' speech during English classes. To achieve this objective, eight speaking lessons for tenth-grade students at Mieraf Primary and secondary school were recorded. Transcriptions were made from these recorded lessons, specifically focusing on classroom exchanges involving teacher initiation, learners' responses, and teacher feedback. The feedback types utilized in the recorded lessons were based on the models proposed by Zahorik (1970) and Chaudron (1977). Furthermore, the frequency of each feedback type found in the recorded lessons was determined and analyzed. In addition to the transcriptions and analysis, questionnaires were administered to four English teachers who taught in the five sections. These teachers were also interviewed to gather their perspectives. The data collected from the questionnaires and interviews were analyzed both quantitatively and qualitatively. The findings revealed that the teachers frequently employed the elaborate praise type of feedback. Moreover, the majority of students expressed positive attitudes toward the feedback they received from their teachers regarding their speech. However, it was noted that a significant number of students expressed the need for feedback from their peers, but only if their teachers provided guidance on how to provide constructive comments to one another. Based on the results, it is recommended that students should be informed about the role of peer feedback in improving their speech. Additionally, teachers should create opportunities for students to enhance their speech skills independently and encourage them to receive feedback from their peers.